A alteridade do real ou da in-condição proletária : ensaio sobre significância e justiça em Emmanuel Levinas - Rodrigues, Tiago dos Santos (2017)
This thesis seeks to present the correlation between significance and justice present in the thought of the Lithuanian-French philosopher Emmanuel Levinas. How the birth of meaning is called to the accomplishment of justice to those close and those far way. The first chapter presents Levianas‘ description of the relation between the existent (the human being) to the existence (the being in general), and how this relation with the being, is in its self, a protest against the being; that is, the necessity of escaping him, once the relation between the human and himself it is not lacking, but in excess which results in oppression. The existent cannot be parted with his existence, his self; he is attached to him; but this same being does not satisfies the aspirations of a, truly, human life. In the search for escape of the condition of being, the human-being may turn to illusory and momentary means of forgetting this being. In the second chapter, it is presented Levinas‘ critic against the philosophies of totality and the neutral, which take their sense of the logic of the being, from his inspiration in the philosophy of Franz Rosenzweing and the critic analyses of what Levinas called at the time of Philosophy of Hitlerism. These philosophies, when working with the ontological logic (symmetry, contemporaneity, equalization), tend to nullify the differences, in another words, the singularities. This in political terms means the legitimation of the state of war and of totalitarian constructions that the multiplicity of terms to a single term. The third chapter presents how of a transcendence to the order of being – the face, unconditional because it does not participate in the conditions of being – the subjectivity of the subject can free oneself of the oppression of excess of being to one of another way to be, with the trauma of the meeting with the face of another that in his misery, indulgence and exposition to death call the subject to the responsibilities. Responsibilities that make the subject, obsessive and make him as if a hostage to another to the maternity mode, in which there is the other in itself, and in which the self, contrary to the logic of being, it is no longer for itself, but it is one to the other, it is significance. The forth chapter presents a brief excursus on the weeping as a way of exposure of the otherness and the discharge of the being, as an expression of way to be. In the fifth and last chapter, it is presented the consequences to the significance of the entry of the third (of the social multiplicity) in the relations with others and how this calls responsibility of the subject to make use, now, of the logic of the being, of ontology, as a role of justice; it is also presented Levianas‘ discretion to the liberal state and of the call that maternal obsession for the other, for the justice, is also call to the revolution, that is, to the freedom of the proletariat of their proletarian condition.